Sikap Peduli Lingkungan Siswa Sesuai Penerapan Kurikulum Merdeka Belajar Pada Materi Perubahan Lingkungan - Gaol, Pelita Lumban; Hasruddin, Hasruddin; Sofia, Sofia (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research uses a descriptive quantitative approach to assess students' environmental awareness in class X E at SMA Negeri 1 Pangururan. The study was conducted from August to October 2024, with the population consisting of 288 students from eight classes. The sample included one biology teacher and 71 students from classes X E 7 and X E 8, selected through simple random sampling. Data were collected using questionnaires and interviews with the teacher. The findings indicate that students have a good attitude toward environmental awareness, with a mean score of 81.99%. The study also highlights factors affecting students' active participation in learning, such as cooperation difficulties and lack of interest in the subject. The research suggests that the Problem-Based Learning model could improve student engagement and environmental awareness.